2016
DOI: 10.12659/msm.897120
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Guidewire Aiming Device to Improve the Accuracy of Guidewire Insertion in Femoral Neck Fracture Surgery Using Cannulated Screw Fixation

Abstract: BackgroundThe aim of this study was to improve the accuracy of guidewire insertion in the femoral neck fracture surgery using cannulated screw fixation.Material/MethodsA novel aiming device was designed and manufactured. Between January 2010 and June 2012, 64 femoral neck fracture patients were included into the study. All 64 patients were divided into 2 groups randomly. The aiming device was used during the operation for patients in the experimental group, but not in the control group.ResultsThere were no sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Special instruments, such as a novel guidewire aiming device (20), a self-designed femoral neck guide pin locator (21), a new adjustable parallel drill guide (22), and robot navigation (23,24) have reportedly been used for the placement of guiding needles. They are believed to have the potential to improve the precision of guide pin insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Special instruments, such as a novel guidewire aiming device (20), a self-designed femoral neck guide pin locator (21), a new adjustable parallel drill guide (22), and robot navigation (23,24) have reportedly been used for the placement of guiding needles. They are believed to have the potential to improve the precision of guide pin insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have developed guides to accurately place Kirschner wires. Yin et al demonstrated a novel guidewire aiming device to improve the accuracy of guidewire insertion [10]. However, the operation was complicated.…”
Section: Discussionmentioning
confidence: 99%
“…[35,10,1214] Accordingly, appropriate placement of guide needles is vital to treat FNF with PCS. [17] The use of a SVMN technique was explored to assist in a PCS insertion.…”
Section: Discussionmentioning
confidence: 99%